Adsorção dos corantes reativos vermelho BF – 4b e amarelo BF – 3r 200% por argila verde-clara. - Carlos, Fernanda Patrícia Santos de Menezes (Universidade Federal Rural do Semi-Árido, 2020)
The segment of textile industry is very present throughout the country due to the constant need of the population for varied clothing. This industrial branch draws attention, standing out within an environmental context due to the large amount of effluents generated, which affects the quality of the water in which it is discharged, after or not some type of previous treatment. Several techniques are being applied in the treatment of these effluents, among them, the adsorption process. This technique is well accepted because of its high efficiency. In this research, it was studied the removal of Reactive Red BF-4B and Yellow BF - 3R 200% dyes from a synthetic effluent through the adsorption process using Cubate Light-Green Clay as an adsorbent. The adsorption tests were carried out in a finite bath with a temperature of 30 ° C and constant agitation of 150 rpm for 24 hours. The analyzes to verify the percentage of removal by adsorption were made by using a spectrophotometer. In order to verify in which conditions the best removal percentages occur, as well as the influence of the study variables in the removal of dyes, experimental plans of the factorial type 22 and central rotational compound were carried out. The studied variables were the ratio between mass of adsorbent per 100 mL of solution and the pH of the solution. The highest percentages of removal were 69,72% for Reactive Red BF-4B Dye and 58,62% for Yellow BF - 3R 200% Dye, showing that the clay is promising for the adsorption process. The linear model proved to be adequate to represent the data adjustment of the removal percentages only for the Reactive Red BF - 4B Dye. The quadratic model proved to be adequate to represent the data adjustment of the removal percentages for both dyes and even more satisfactorily than the linear model.
Keywords: Adsorção; argila verde-clara; corante reativo; ENGENHARIAS::ENGENHARIA QUIMICA